Acute kidney injury associated with Yersinia pseudotuberculosis infection: Forgotten but not gone - Ye Kyung Kim; Myung Hyun Cho; Hye Sun Hyun; Eujin Park; Il-Soo Ha; Hae Il Cheong; Hee Gyung Kang (The Korean Society of Nephrology, 2019)
Background : Yersinia pseudotuberculosis is known to cause fever, gastroenteritis, or acute kidney injury (AKI). There have been several Y. pseudotuberculosis infection outbreaks to date associated with ingestion of contaminated food or unsterile water. While this disease was considered to have practically been eradicated with the improvement in public health, we encountered several cases of AKI associated with Yersinia infection. Methods : We retrospectively collected data from medical records of patients with suspected Y. pseudotuberculosis infection who visited Seoul National University Children's Hospital in 2017. Results : There were nine suspected cases of Yersinia infection (six males and three females; age range 2.99-12.18 years). Among them, five cases occurred in May, and seven patients were residing in the metropolitan Seoul area. Three patients had history of drinking mountain water. Every patient first presented with fever for a median of 13 days, followed by gastrointestinal symptoms and oliguria. Imaging studies revealed mesenteric lymphadenitis, terminal ileum wall thickening, and increased renal parenchymal echogenicity. Creatinine levels increased to 5.72 ± 2.18 mg/dL. Urinalysis revealed sterile pyuria, proteinuria, and glycosuria. Oliguria continued for 4 to 17 days, and two patients required dialysis; however, all of them recovered from AKI. Mucocutaneous manifestations developed later. In the diagnostic work-up, Yersinia was isolated from the stool culture in one patient. Anti-Yersinia immunoglobulin (Ig) A and IgG were positive in 6 patients. Conclusion : Y. pseudotuberculosis infection is an infrequent cause of interstitial nephritis presenting with AKI. When a patient presents with fever, gastroenteritis, and AKI not resolving despite hydration, the clinician should suspect Y. pseudotuberculosis infection.